1984
DOI: 10.1084/jem.160.5.1591
|View full text |Cite
|
Sign up to set email alerts
|

A multivalent lacto-N-fucopentaose III-lysyllysine conjugate decompacts preimplantation mouse embryos, while the free oligosaccharide is ineffective.

Abstract: The carbohydrate chains of glycolipids and glycoproteins at the cell surface are known to undergo many rapid changes during embryogenesis. These developmental changes include (a) alteration of branching structure in lactoseries carbohydrate chains, identified as I/i interconversion (1), (b) modification of terminal chains, responsible for the transition from Ii to ABH or SSEA-1 (reviewed in 2), (c) transition of globoseries antigen expression through pk, p, and Forssman (3), and (d) switching of core structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
122
0
4

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(127 citation statements)
references
References 16 publications
1
122
0
4
Order By: Relevance
“…Previous studies from our group and others have demonstrated that glycosphingolipids (GSLs) mediate cell adhesion (12)(13)(14)(15), and they modulate cell growth through their effect on growth factor receptor tyrosine kinases (16)(17)(18)(19)(20). In addition, we have demonstrated that some GSLs, particularly gangliosides, play an essential role in defining cell motility through their interaction with integrins and tetraspanin CD9 or CD82 (21,22).…”
mentioning
confidence: 90%
“…Previous studies from our group and others have demonstrated that glycosphingolipids (GSLs) mediate cell adhesion (12)(13)(14)(15), and they modulate cell growth through their effect on growth factor receptor tyrosine kinases (16)(17)(18)(19)(20). In addition, we have demonstrated that some GSLs, particularly gangliosides, play an essential role in defining cell motility through their interaction with integrins and tetraspanin CD9 or CD82 (21,22).…”
mentioning
confidence: 90%
“…This antigen first appears on the surface of cells at the eight-cell stage of mouse embryogenesis and later becomes restricted to specific cell types during murine development (Solter and Knowles 1978;Pennington et al 1985). Complementary experimental observations by two groups suggest that the SSEA-1 antigen may participate in adhesive events leading up to and involving compaction (Bird and Kimber 1984;Fenderson et al 1984). Although the molecular nature of these processes is undefined, recent biochemical evidence suggests that homotypic carbohydrate-carbohydrate interactions between SSEA-1 molecules may be operative in this context (Eggens et al 1989).…”
mentioning
confidence: 98%
“…These patterns are discernible first on the surfaces of preimplantation and early postimplantation embryomc cell aggregates (Bird and Kimber 1984;Fenderson et al 1984;Pennington et al 1985;Fenderson et al 1986;Kimber 1986). In the mature organism, expression of distinct oligosaccharide moieties ultimately becomes restricted to specific cell types (Szulman 1960(Szulman , 1962Watkins 1980;Dodd and Jessel 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are found at various stages of development. These include the extension or shortening of carbohydrate polymers, such as polysialic acid [3] on the neural cell-adhesion molecule, the presence of fucosyl residues in al-3 linkage to Gal(jI1-4)GlcNAc on glycoconjugates [Fuc(al-3)GlcNAc] associated with particular stages of the embryo [4], the response to the Zucto-N-fucopentaose-I11 complex during compaction of the embryo [5] and the addition of sialic acid residues to a glycoprotein in a-2,6 linkage to galactose during maturation of lymphocytes [6].…”
mentioning
confidence: 99%